Nitrogen Surplus Displays a Spurious Environmental Kuznets Curve in Germany - Bente Castro Campos; Martin Petrick (German Journal of Agricultural Economics (GJAE), 2023)
We examine the relationship between nitrogen surplus per hectare and the median monthly wage per capita considering the Environmental Kuznets Curve (EKC) theory. The EKC hypothesizes an inverse U-shape relationship between environmental pollution and per capita income. We use a novel panel data set for nitrogen surplus as an environmental pollutant and a measure of the median monthly wage per capita during the period from 1999 to 2018 for 401 counties in Germany. Our estimation results show that nitrogen surplus displays a spurious EKC in Germany. It is spurious because the inverse U-shape relationship of nitrogen surplus and median wage is rejected by almost all model specifications and by tracing of individual county paths. This implies that in Germany economic growth has not cleaned up the environmental damage from nitrogen surplus. The affected counties remain in a spatial cluster (shown with the individual county paths) that they cannot break out of in the course of the EKC, at least not without political intervention.
Keywords: 330